Coarse-Grained Modeling of Coronavirus Spike Proteins and ACE2 Receptors - Leong, Timothy; Voleti, Chandhana; Peng, Zhangli (Frontiers in Physics, 2021)
We developed coarse-grained models of spike proteins in SARS-CoV-2 coronavirus and angiotensin-converting enzyme 2 (ACE2) receptor proteins to study the endocytosis of a whole coronavirus under physiologically relevant spatial and temporal scales. We first conducted all-atom explicit-solvent molecular dynamics simulations of the recently characterized structures of spike and ACE2 proteins. We then established coarse-grained models using the shape-based coarse-graining approach based on the crystal structures, and extracted the force field parameters from the all-atom simulation trajectories. To further analyze the coarse-grained models, we carried out normal mode analysis of coarse-grained models to refine the force field parameters by matching the fluctuations of the internal coordinates with the original all-atom simulations. Finally, we demonstrated the capability of these coarse-grained models by simulating the endocytosis of an entire coronavirus. We embedded the coarse-grained models of spike proteins on the surface of the virus envelope and anchored ACE2 receptors on the host cell membrane, which is modeled using a one-particle-thick lipid bilayer model. The coarse-grained simulations show the spike proteins adopt bended configurations due to its unique flexibility during their interaction with the ACE2 receptors, which makes it easier for them to attach to the host cell membrane than rigid spikes.